Lungworm Eucoleus aerophilus (Capillaria aerophila) infection in a feline immunodeficiency virus-positive cat in France. Issue 1 (June 2016) - Elhamiani Khatat, Sarah; Rosenberg, Dan; Benchekroun, Ghita; Polack, Bruno
Case summary: A 2-year-old domestic shorthair female outdoor cat living in France was diagnosed with a lungworm infection due to Eucoleus aerophilus . The history and clinical signs, in association with bronchoscopic examination, suggested chronic upper respiratory disease. Cytological examination of bronchoalveolar lavage fluid (BALF) was consistent with suppurative bronchitis. Direct microscopic examination of BALF enabled the identification of E aerophilus ova. Relevance and novel information: The cat was positive for feline immunodeficiency virus and had been treated with steroids for a suspected allergic bronchitis, suggesting that immunodeficiency was probably a facilitating factor for E aerophilus infection, as described in previous cases. This case report emphasises the importance of considering eucoleosis (capillariosis) in the differential diagnosis of respiratory disease in cats. To our knowledge, this is the first clinical case of E aerophilus infection described in a domestic cat in France.